Sensitive Materials for Chemical Agents Vapor Detection Using SAW Sensors. (2016) - Minot, Benoit; Frenois, Celine; Besnard, Stephanie; Bordet, Jeremy; Martins, Nathalie; Pereira, Franck
Abstract: Since the last decade, developments of devices to detect chemical agents (CAs) are greatly developed. SAW technology presents the advantage of rapid respond to chemical, good sensitivity and selectivity and an interesting potential of miniaturization. Selected polymer films were coated on SAW chemical sensors and expose to relevant mimics. Specific improvement was realized to enhance signal response and selectivity using micro spray coating and specific processing including the entire selected polymer for better target recognition.